Relationship Between Perineal Wound Pain Degree and PRP Healing in Vaginal Birth - Fatima Diyas Zahra; Bobby Indra Utama; Almurdi Almurdi; Roza Sri Yanti; Deddy Saputra; Nelmi Silvia (Andalas Obstetrics And Gynecology Journal, 2026)
Introduction : This study aims to see the relationship between the level of perineal wound pain and healing using PRP (Platelet Rich Plasma) in Vaginal birth. Perineal wound pain causes fear of movement resulting in subinvolution, unsmooth release of the locea, bleeding, or infection. Method : This type of research is Experimental with chi-quadrath design . The intervention group received PRP injections on perineal wounds on day 1 after delivery, while the control group was the group that was not given PRP. On the 7th day, observation of the degree of pain of perineal wounds was carried out using the VAS scale (Visual Analog Scale) in both groups. Result : The results of the study obtained a value of p=0.016. Then the value of OR = 6.250 was also obtained. Conclusion : there is a significant relationship between the level of perineal wound pain and healing using PRP in Vaginal birth. From the OR score, it is known that patients who receive PRP have a 6.25 times chance of experiencing mild pain compared to patients who are not given PRP. Keywords : pain; perineal wound; PRP; Vaginal birth.